2016
DOI: 10.1186/s12903-016-0272-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity on the outcome of non-surgical periodontal therapy - a systematic review

Abstract: Background: Obesity and periodontitis are important chronic health problems. Obesity is associated with an increased prevalence of periodontitis. Whether obesity also affects the outcome of non-surgical periodontal therapy is to date still unclear. Methods: A systematic review of studies referenced in SCOPUS, MEDLINE, PubMed, Cochrane, CINAHL, Biosis and Web of Science was performed. Titles, abstracts and finally full texts were scrutinized for possible inclusion by two independent investigators. Quality and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 130 publications
2
23
0
1
Order By: Relevance
“…A strength of this study was minimization of confounding factors through the exclusion of smokers and diabetics from the study sample, factors similarly reported in some previously published evidence (Gerber et al, ; Lakkis et al, ; Nascimento, Leite, Correa, Peres, & Demarco, ). Further strengths included the 6‐month follow‐up with no change in BMI status, which is longer than some previous studies (Al‐Zahrani & Alghamdi, ; Duzagac et al, ; Eldin, Nasr, & Hassan, ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A strength of this study was minimization of confounding factors through the exclusion of smokers and diabetics from the study sample, factors similarly reported in some previously published evidence (Gerber et al, ; Lakkis et al, ; Nascimento, Leite, Correa, Peres, & Demarco, ). Further strengths included the 6‐month follow‐up with no change in BMI status, which is longer than some previous studies (Al‐Zahrani & Alghamdi, ; Duzagac et al, ; Eldin, Nasr, & Hassan, ).…”
Section: Discussionmentioning
confidence: 65%
“…In particular, obese subjects had less favourable reductions in full‐mouth mean probing pocket depths and the percentage of sites presenting with probing pocket depth >4 mm at 2 months following non‐surgical periodontal therapy when compared to non‐obese individuals (Suvan et al, ). Results from prospective studies conducted to investigate the effect of obesity on periodontal therapy outcomes have provided variable results possibly due to small sample size, differing lengths of follow‐up and the presence of confounding factors such as smoking as potential sources of heterogeneity; therefore, additional evidence from larger studies is merited (Akram et al, ; Gerber et al, ; Goncalves et al, ). The aim of this study was to ascertain whether obesity is a predictor of the response to non‐surgical periodontal therapy based upon clinical periodontal assessment measured at 2 and 6 months following therapy in non‐smoker BMI obese and BMI normal individuals suffering from moderate to severe periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 1 study based analysis of the effect of obesity on response to treatment between study groups on sites with probing depths ≥4 mm following treatment no statistically significant difference was shown. 157 This study was 1 of 3, included in the review by Gerber et al, 133 which did not demonstrate a difference in periodontal clinical parameters in obese versus nonobese subjects following treatment. Five of 8 studies in this review did report poorer clinical responses to periodontal treatment in obese compared with nonobese subjects, with the comment that the effect was specifically observed in moderate-to-deep pockets.…”
Section: Experimental Onlymentioning
confidence: 95%
“…Akram et al (2016) 131 Gerber et al (2016) 133 Nascimento et al (2016) 140 Papageorgiou et al (2015) 142…”
Section: Publication Yearmentioning
confidence: 99%
See 1 more Smart Citation